Bortezomib in multiple myeloma - Terpos, E.; Roussou, M.; Dimopoulos, M.-A. (Expert Opinion on Drug Metabolism and Toxicology, 2008)
Background: Bortezomib is a novel, first-in-class proteasome inhibitor that has improved outcomes in multiple myeloma. with manageable toxicities. Objective: To summarise the chemistry, pharmacokinetics and metabolism of bortezomib, and review its clinical efficacy and toxicity, including use in elderly patients, use in patients with renal impairment and/or a poor prognosis, and effects on bone metabolism. Methods: Literature search of bortezomib studies (within 10 years) and recent congress abstracts. Results/conclusions: Bortezomib has improved response rates, overall survival, and time to progression in relapsed or refractory disease, both as a single agent and as part of combination regimens. Promising results have also been reported with bortezomib combinations in frontline induction therapy. Patient subgroups where conventional approaches are inappropriate may also benefit, thereby expanding the therapeutic armamentarium against this debilitating disease. © 2008 Informa UK Ltd.
Keywords: Bone disease; bortezomib; Frontline; induction; multiple myeloma; Proteasome inhibitors; refractory; relapsed